Evaluating the Impacts of an In-service Teacher Training Course on Kurdish EFL Basic School Teachers - Hassan, Asst. Prof. Dr. Zana M.; Kheder, Lecturer: Rasool Mohammed (Sulaimani Journal for Humanities, 2023)
The present study which is an extract from a PhD dissertation evaluates and explores the impact of an in-service training course, designed by the researchers, on EFL-BKTs. The study mainly intends to identify the effectiveness of the course on trainee teachers’ beliefs, knowledge, skills and classroom practices. For this purpose, the Kirkpatrick-Katzell’s four-level model has been employed. A convergent parallel design, a mixed- method (quantitative and qualitative) approach and various data collection instruments including a questionnaire, a focus group discussion and lesson observation tools are utilised for the current case study. The findings revealed that designed INSETT course had positive impact on in-service teacher trainees at all four levels of the applied model.
Keywords: Inservice Teacher Training (INSETT); English as a Foreign LanguageBasic school Kurdish Teachers (EFLBKTs); KirkpatrickKatzells Model; Course Evaluation